Occlusal Reconstruction Aided by Electronic Face Bow - Miss Anna Qiu; Mrs Rui He (Elsevier, 2023)
Introduction: This is a case of occlusal reconstruction aided by electronic face bow, and successfully restored the normal occlusal relationship, the normal vertical distance, and the ideal occlusal plane. Case Description: A 35-year-old female, attended with a chief complain of "unstable occlusion of bilateral posterior teeth after joint treatment for several months". Physical examination showed that during mouth movement, the left temporomandibular joint movement is weaker than the right, with the opening type slightly to the left; there is no extensive and stable occlusion contact between bilateral posterior teeth during centric occlusion. We used intraoral scanner and electronic face bow to record the basic information and designed the interim restorations to get the intercuspal position (ICP). After all dental problems were cured, we started to prepare the teeth and wear interim restorations. With continuous adjustment, the most suitable and stable occlusal relationship of the joint was obtained. The mandibular movement trajectory becomes symmetrical and stable. Scanned the occlusal relationship again for the definitive restorations. During the whole restoration procedure, the patient had no significant discomfort in temporomandibular joint movements. Discussion: Aided by electric face bow, the digital form of the patient's mandibular motion before and after treatment can be visualized in the computer. Compared with the traditional occlusal reconstruction, it can precisely transfer dynamic and static occlusion, and easier to obtain the most ideal occlusion relationship and assist in the design of the restorations with successful definitive reconstructions. Conclusion/Clinical Significance: Electric face bow has its unique advantages in occlusal reconstruction and is suitable for widespread application in clinical practice.